2020
DOI: 10.1007/s12553-020-00446-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning prediction of susceptibility to visceral fat associated diseases

Abstract: Classifying subjects into risk categories is a common challenge in medical research. Machine Learning (ML) methods are widely used in the areas of risk prediction and classification. The primary objective of such algorithms is to use several features to predict dichotomous responses (e.g., healthy/at risk). Similar to statistical inference modelling, ML modelling is subject to the problem of class imbalance and is affected by the majority class, increasing the false-negative rate. In this study, we built and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Another limitation observed in this study is the low amount of positive imaging results, since the effectiveness of a computational model can be reduced if there is a class imbalance, since most of the time, the majority group tends to overcome the minority, increasing the probability of false-negative results [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation observed in this study is the low amount of positive imaging results, since the effectiveness of a computational model can be reduced if there is a class imbalance, since most of the time, the majority group tends to overcome the minority, increasing the probability of false-negative results [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that applying the correct level of resampling without disrupting the original data distribution in the RUS-based method, together with the desired choice of performance metrics and slight manipulation of IG levels, produced a good prediction solution [66]. The RF-RUS model competed with further developed models with algorithmic modifications in the case of cost-sensitive classification.…”
Section: Discussionmentioning
confidence: 89%
“…Te SMOTE selects a point at random from the minority class and calculates its K-nearest neighbors for this point [17,18]. Between the selected point and its neighbors, the artifcial points are inserted.…”
Section: Datasetmentioning
confidence: 99%